FcγRIIb Expression Is Decreased on Naive and Marginal Zone-Like B Cells From Females With Multiple Sclerosis - Stephanie Trend; Stephanie Trend; Jonatan Leffler; Ingrid Teige; Björn Frendéus; Allan G. Kermode; Allan G. Kermode; Martyn A. French; Prue H. Hart (Frontiers in Immunology, 2021)
B cells are critical to the development of multiple sclerosis (MS), but the mechanisms by which they contribute to the disease are poorly defined. We hypothesised that the expression of CD32b (FcγRIIb), a receptor for the Fc region of IgG with inhibitory activities in B cells, is lower on B cell subsets from people with clinically isolated syndrome (CIS) or MS. CD32b expression was highest on post-naive IgM+ B cell subsets in healthy controls. For females with MS or CIS, significantly lower CD32b expression was identified on IgM+ B cell subsets, including naive and IgMhi MZ-like B cells, when compared with control females. Lower CD32b expression on these B cell subsets was associated with detectable anti-Epstein Barr Virus viral capsid antigen IgM antibodies, and higher serum levels of B cell activating factor. To investigate the effects of lower CD32b expression, B cells were polyclonally activated in the presence of IgG immune complexes, with or without a CD32b blocking antibody, and the expression of TNF and IL-10 in B cell subsets was assessed. The reduction of TNF but not IL-10 expression in controls mediated by IgG immune complexes was reversed by CD32b blockade in naive and IgMhi MZ-like B cells only. However, no consequence of lower CD32b expression on these cells from females with CIS or MS was detected. Our findings highlight a potential role for naive and marginal zone-like B cells in the immunopathogenesis of MS in females, which requires further investigation.